Geographical location and age affects the incidence of parasitic infestations in school children - Rayan Paran; Verghese Susan; McDonnell Pauline (Wolters Kluwer Medknow Publications, 2010)
Environmental factors affect the dissemination and distribution of intestinal parasites in human communities. To comprehend the prevalence of parasitic infestation and to examine whether geographical location and age also influence the prevalence of infection, fecal samples from 195 school children (rural = 95; male = 39; female = 56) (urban = 100; male = 60; female = 40) of five age groups ranging from 5 to 11 years in two different socio-economic zones (rural and urban) were screened for specific intestinal parasites using standard histological techniques. Percentage incidences of parasitic species found in fecal wet mounts and concentrates in rural children were Entamoeba coli (25.3%), Giardia lamblia (17.9%), Blastocystis hominis (14.7%), Entamoeba histolytica (4.2%), Iodamoeba butschlii (1.1%), Hymenolepis nana (1.1%) and Ascaris lumbricoides (1.1%). Whereas the percentage incidences among urban children were E. coli (26%), A. lumbricoides (21%), B. hominis (18%), G. lamblia (14%), T. trichiura (8%), I. butschlii (4%) and A. duodenale (1%). Such findings may be related to dietary differences, living conditions and the greater use of natural anti-helminthic medicinal plants in rural communities. These results are important for both epidemiological data collection and for correlating dietary differences to intestinal parasitic diseases. Aims: We chose to investigate whether geographical location and age affect the prevalence and distribution of intestinal parasites among school children from two separate regions (rural and urban) in areas surrounding, Chennai, Tamil Nadu, India. Settings and Design: A study of the prevalence of parasitic infestations was undertaken among primary school children, in rural and urban communities around Chennai, Tamil Nadu, India. Materials and Methods: Faecal sample collection, direct microscopic techniques, macroscopic examination and concentration techniques for identifying the parasites. Statistical analysis used: Percentage incidences of parasitic species found in faecal wet mounts and concentrates were done instead of statistical analyses. Results: Both macroscopic and microscopic examinations of faecal samples revealed that the overall percentage prevalence of parasite species encountered in rural children were Entamoeba coli (25.3%), G. lamblia (17.9%), B. hominis (14.7%), Entamoeba histolytica (4.2%), I. butschlii (1.1%), H. nana (1.1%), Ascaris lumbricoides (1.1%). The prevalence among urban children were E. coli (26%), A. lumbricoides (21%), B. hominis (18%), G. lamblia (14%), T. trichiura (8%), I. butschlii (4%) and A. duodenale (1%). Overall, comparative significant differences were noted between rural and urban children for E. histolytica (4.2 vs. 14%), G. lamblia (17.9 vs. 14%), A. lumbricoides (1.1 vs. 21%) and T. trichiura (0 vs. 8%), with the major difference being the much higher occurrence of A. lumbricoides and T. trichiura infections in urban children. Conclusions: One of the greatest challenges for healthcare professionals is the prevention and treatment of protozoal and helminthic parasitic infections. From our study we conclude that the prevalence of different pathogenic species of amoeba such as Entamoeba histolytica (4.2 vs. 0%) and G. lamblia (17.9 vs. 14%), (P value was equal to 1) was significantly higher among rural children compared to children from urban areas. In contrast, the prevalence of nematodes such as A. lumbricoides (21% vs. 1.1%), T. trichiura (8% vs. 0%) and A. duodenale (1%) was also significantly higher among rural children.